Positioning : the battle for your mind - Ries, Al; Trout, Jack (McGraw Hill-Ascent Audio, 2023)
The first book to deal with the problems of communicating to a skeptical, media-blitzed public, Positioning describes a revolutionary approach to creating a "position" in a prospective customer's mind-one that reflects a company's own strengths and weaknesses as well as those of its competitors. Advertising gurus Ries and Trout explain how to make and position an industry leader so that its name and message wheedles its way into the collective subconscious of your market-and stays there; position a follower so that it can occupy a niche not claimed by the leader; and avoid letting a second product ride on the coattails of an established one. Positioning also shows you how to use leading ad agency techniques to capture the biggest market share and become a household name; build your strategy around your competition's weaknesses; reposition a strong competitor and create a weak spot; use your position to its best advantage; choose the best name for your product; determine when-and why-less is more; and analyze recent trends that affect your positioning. Ries and Trout provide valuable case histories and penetrating analyses of some of the most phenomenal successes and failures in advertising history. Revised to reflect significant developments since its original publication, Positioning is a must-listen for anyone in business today